2022
DOI: 10.21303/2504-5695.2022.002409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxic activity of live toxoplasma gondii tachyzoites and toxoplasma antigen on MCF-7 human breast cancer cell line

Abstract: The aim of this study was to investigate the cytotoxic potency of live Toxoplasma gondii tachyzoites as well as Toxoplasma antigen on MCF-7 human breast cancer cell line. Cancer cell lines are considered an essential preliminary step towards in-vitro investigation of the potential antineoplastic impact of novel chemotherapeutic agents. Pathogens, including viruses, bacteria, and parasites are noticeably under investigation, considering their potential antineoplastic activity. Some have attained a steady positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…According to the recent research progress, it is worth mentioning that the components of T. gondii have good potential for anti-tumor applications. Eissa et al demonstrated that mice immunized with autoclaved Toxoplasma vaccine (ATV) produced 13.3% inhibition of Ehrlich solid carcinoma (ESC) genesis and confirmed the existence of at least four pairs of common antigens between ATV and ESC (Eissa et al, 2023). Subsequent results showed that ATV and cyclophosphamide synergistically exerted a stronger tumor immune response and anti-angiogenesis effect in ESC-bearing mice, indicating that ATV has the potential to be a tumor vaccine or cancer drug adjuvant (Ismail et al, 2023).…”
Section: Anti-tumor Potential Of T Gondii Componentsmentioning
confidence: 98%
“…According to the recent research progress, it is worth mentioning that the components of T. gondii have good potential for anti-tumor applications. Eissa et al demonstrated that mice immunized with autoclaved Toxoplasma vaccine (ATV) produced 13.3% inhibition of Ehrlich solid carcinoma (ESC) genesis and confirmed the existence of at least four pairs of common antigens between ATV and ESC (Eissa et al, 2023). Subsequent results showed that ATV and cyclophosphamide synergistically exerted a stronger tumor immune response and anti-angiogenesis effect in ESC-bearing mice, indicating that ATV has the potential to be a tumor vaccine or cancer drug adjuvant (Ismail et al, 2023).…”
Section: Anti-tumor Potential Of T Gondii Componentsmentioning
confidence: 98%